Efficacy of the Reactive Oxygen Species Generated by Immobilized TiO2 in the Photocatalytic Degradation of Diclofenac. (27th May 2015) - Di Credico, B.; Bellobono, I. R.; D'Arienzo, M.; Fumagalli, D.; Redaelli, M.; Scotti, R.; Morazzoni, F.
Abstract : We report on the photodegradation of diclofenac (DCF) by hydrothermal anatase nanocrystals either free or immobilized in porous silica matrix (TS) in connection to the type and amount of reactive oxygen species (ROS), in order to have deeper insight into their role in the photocatalysis and to provide an effective tool to implement the DCF mineralization. TiO2 and TS exhibit a remarkable efficiency in the DCF abatement, supporting that the utilization of anatase nanoparticles with the highly reactive{ 001 }, { 010 }, and{ 101 } exposed surfaces can be an effective way for enhancing the photooxidation even of the persistent pollutants. Furthermore, the hydrothermal TiO2, when immobilized in silica matrix, preserves its functional properties, combining high photoactivity with an easy technical use and recovery of the catalyst. The catalysts performances have been related to the presence of OH, O 2 1, andO 2 - species by electron paramagnetic resonance spin-trap technique. The results demonstrated that the ROS concentration increases with the increase of photoactivity and indicated a significant involvement ofO 2 1 in the DCF degradation. The efficacy of TiO2 when immobilized on a silica matrix was associated with the high ROS life time and with the presence of singlet oxygen, which contributes to the complete photomineralization of DCF.